Development and validation of a novel nomogram for prediction of ketosis-prone type 2 diabetes - Min, Rui; Liao, Yiqin; Peng, Bocheng (Frontiers in Endocrinology, 2023)
Background Ketosis-prone type 2 diabetes (KPD), as a unique emerging clinical entity, often has no clear inducement or obvious clinical symptoms at the onset of the disease. Failure to determine ketosis in time may lead to more serious consequences and even death. our study aimed to develop and validate a novel nomogram to predict KPD. Methods clinical data of a total of 398 newly diagnosed type 2 diabetes who met our research standards with an average age of 48.75±13.86 years years old from January 2019 to December 2022 were collected. According to the occurrence of ketosis, there were divided into T2DM groups（228 cases）with an average age of 52.19±12.97 years, of whom 69.74% were male and KPD groups （170cases）with an average age of 44.13±13.72 years, of whom males account for 80.59%. Univariate and multivariate logistic regression analysis was performed to identify the independent influencing factors of KPD and then a novel prediction nomogram model was established based on these independent predictors . Verification and evaluation of predictive model performance comprised ROC curve, corrected calibration curve, and DCA curve Results 4 primary independent predict factors of KPD were identified by univariate and multivariate logistic regression analysis and entered into the nomogram including age, family history, HbA1c and FFA. The model incorporating these 4 predict factors displayed good discrimination to predict KPD with the area under the ROC curve (AUC) of 0.945. The corrected calibration curve of the nomogram showed good fitting ability with an average absolute error =0.006 < 0.05, indicating a good accuracy. The (DCA) curve demonstrated that when the risk threshold was between 5% and 99%, the nomogram model was more practical and accurate. Conclusion In our novel prediction nomogram model, we found that age, family history, HbA1c and FFA were the independent predict factors of KPD. The proposed nomogram built by these 4 predictors was well developed and exhibited powerful predictive performance for KPD with high discrimination, good accuracy, and potential clinical applicability, which may be a useful tool for early screening and identification of high-risk population of KPD and therefore help clinicians in making customized treatment strategy.